2003
DOI: 10.1108/02637470310495009
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating workplace utility

Abstract: The research discussed in this paper is part of an ongoing doctoral study funded by Sheffield Hallam University. The authors would like to thank Joe Cassidy at the Department for Education and Skills for assistance in conducting the research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 11 publications
2
74
1
Order By: Relevance
“…A theoretical framework consisting of 11 workplaces attributes as items was selected through a literature review. 5 It includes four items that were included in a highly reliable construct developed by Pinder of office facility utility (Pinder et al, 2003). However, through the literature review it was identified that occupant perception towards consumption within their office facility may be equally as significant as utility (Dasgupta, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical framework consisting of 11 workplaces attributes as items was selected through a literature review. 5 It includes four items that were included in a highly reliable construct developed by Pinder of office facility utility (Pinder et al, 2003). However, through the literature review it was identified that occupant perception towards consumption within their office facility may be equally as significant as utility (Dasgupta, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The item scale considered the effects of the indoor environment, functionality, aesthetic appearance, and configuration on workplace satisfaction. The resulting framework was demonstrated to be a highly reliable measure, with a Cronbach's Alpha of 0.93, achieved through replacing missing data with the calculated mean of the corresponding items (Pinder et al, 2003). Cronin & Taylor disputed SERVQUAL measures as lacking theoretical and empirical support.…”
Section: Previous Studies Measuring Satisfactionmentioning
confidence: 99%
“…The technical lifespan is the period of time during which the property can meet the technical and physical demands required to use the building and to protect the health and safety of occupants. Whereas the functional lifespan is the period during which a property complies with user's functional demands [21]. Clearly the three types of lifespan are interrelated.…”
Section: Sustainability In Adaptive Reusementioning
confidence: 99%
“…Parasuraman et al (1985) take it one step further, stating the quality evaluation is not solely based on the outcome of a service; the process of the service delivery is taken in account as well. At the same time, simply accommodating the tenant's specific needs can influence retention equity-needs which customers often find difficult to articulate (Pinder et al, 2003), making the evaluation of customer satisfaction difficult. This difficulty in taking everything into consideration when designing the evaluation and measuring customer satisfaction is one of the main arguments for the perceived performance evaluations (Johnson et al, 2001).…”
Section: Measuring Customer Satisfactionmentioning
confidence: 99%
“…Focusing on current customers' needs can be rewarding; therefore, the real estate industry concentrates on retaining their customers instead of attracting new tenants. Pinder et al (2003) also stress the importance of tenants and the rewards of treating them as valued customers.…”
Section: Customer Satisfaction In the Context Of Real Estate Managementmentioning
confidence: 99%